Culture and mental health: Towards cultural competence in mental health delivery - Temitope OGUNDARE (Journal of Health and Social Sciences)
The purpose of this paper is to highlight the role of culture in the conceptualization of mental illness and the phenomenology of mental illness across cultures. Mental health professionals are increasingly dealing with a multicultural patient population and there is an urgent need for awareness of the influence of culture in understanding patient’s expression of distress, assigning symptoms to a diagnostic category and planning treatment in culturally appropriate ways. Cultural bias can lead to misdiagnosis and have devastating consequences on patients. This paper highlights the need for cultural competency in mental health service delivery and outlines ways mental health professionals can think about the issue of culture in their practice.